Shameless. The complete eighth season [videorecording (DVD)] - Macy, William H., 1950-; Rossum, Emmy, 1986-; White, Jeremy Allen (Warner Bros. Home Entertainment, 2018)
Frank comes out of a drug-induced haze and decides it's finally time to be a contributing member of society. Fiona faces hard decisions when she discovers her success as a landlord may mean someone else's misfortune. Lip struggles with staying sober, while Ian takes up a cause in hopes of getting back with Trevor. Debbie builds her future at welding school while juggling life as a single working mom, as Carl gets creative finding tuition money after he loses his scholarship.